Development of a practice-based research program. - Hawk C; Long CR; Boulanger K (Journal of Manipulative & Physiological Therapeutics)
OBJECTIVE: To establish an infrastructure to collect accurate data from ambulatory settings. DESIGN: The program was developed through an iterative model governed by a process of formative evaluation. The three iterations were a needs assessment, feasibility study and pilot project. Necessary program components were identified as infrastructure, practitioner-researcher partnership, centralized data management and standardized quality assurance measures. SETTING AND PARTICIPANTS: Volunteer chiropractors and their staff collected data on patients in their practices in ambulatory settings in the U.S. and Canada. OUTCOME MEASURES: Evaluative measures were counts of participants, patients and completed forms. Standardized, validated and reliable measures collected by patient self-report were used to assess treatment outcomes. These included the SF-36 or SF-12 Health Survey, the Pain Disability Index, and the Global Well-Being Scale. For characteristics for which appropriate standardized instruments were not available, questionnaires were designed and and pilot-tested before use. RESULTS: Information was gathered on practice and patient characteristics and treatment outcomes, but for this report, only those data concerning process evaluation are reported. Through the three program iterations, 65 DCs collected data on 1360 patients, 663 of whom were new patients. Follow-up data recorded by doctors were obtained for more than 70% of patients; a maximum of 50% of patient-completed follow-up forms were collected in the three iterations. CONCLUSIONS: This program is capable of providing data for descriptive epidemiology of ambulatory patients, and, with continued effort to maximize follow-up, may have utility in providing insight into utilization patterns and patient outcomes.